Barriers of Supply Chain Management in International Market for Malaysian Food and Beverage Franchisors - Nurul Ashykin, Abd Aziz; Mohd Hizam, Hanafiah; Mohamad Rohieszan, Ramdan; Mohd Nasrulddin, Abd Latif; Nurul Aien, Abd Aziz; Zuraidah, Zainol (Penerbit Universiti Kebangsaan Malaysia, 2022)
Supply chain management activities are becoming increasingly important to maintain efficient operations for franchisors in international markets. However, there are gaps related to barriers that affect these activities. Thus, the aim of this research is to explore the barriers experienced by Malaysian franchisors. A qualitative approach through four case studies was conducted with Malaysian food and beverage franchisors as part of the methodology section. The themes developed are: (i) complications of supply chain network; (ii) challenges in finding the right supplier; (iii) difficulties in logistics and transportation; and (iv) accessibility of central kitchen location. Theoretically, this study improves the existing literature on franchising international supply chains through Resource Dependence Theory. Practically, this study provides useful guidance to franchisors to find appropriate and good sources and suppliers when they expand into the international market, be a reference to related parties for policy development and coordinate the supply chain management of the franchise system in the international market in an effective and planned manner.